A qualitative study of clinicians’ experience of a clinical trial for displaced distal radius fractures - Phelps, EE; Tutton, E; Costa, ML; Achten, J; Gibson, P; Perry, DC (British Editorial Society of Bone and Joint Surgery, 2024)
Aims: The aim of this study was to explore clinicians’ experience of a paediatric randomized controlled trial (RCT) comparing surgical reduction with non-surgical casting for displaced distal radius fractures. Methods: Overall, 22 staff from 15 hospitals who participated in the RCT took part in an interview. Interviews were informed by phenomenology and analyzed using thematic analysis. Results: Analysis of the findings identified the overarching theme of “overcoming obstacles”, which described the challenge of alleviating staff concerns about the use of non-surgical casting and recruiting families where there was treatment uncertainty. In order to embed and recruit to the Children’s Radius Acute Fracture Fixation Trial (CRAFFT), staff needed to fit the study within clinical practice, work together, negotiate treatment decisions, and support families. Conclusion: Recruiting families to this RCT was challenging because staff were uncertain about longer-term patient outcomes, and the difficulties were exacerbated by interdisciplinary tensions. Strong family and clinician beliefs, coupled with the complex nature of emergency departments and patient pathways that differed site-by-site, served as barriers to recruitment. Cementing a strong research culture, and exploring families’ treatment preferences, helped to overcome recruitment obstacles.